Kościół domem a biskup ojcem w świetle Konstytucji Apostolskich i innych pism syryjskich od I do V wieku - Żelazny, Jan W. (Verbum Vitae, 2011)
The model of fatherhood in the Eastern Church of the first centuries was bound, on the one hand, to the biblical idea of God the Father and, on the other hand, to the image of the Church perceived as a household with the bishop being a father. At that point the three issues should be stressed: 1) The authority of bishop as a father is rooted in the authority of God the Father; 2) The fatherly care of bishop embraces not only religious issues but extends to all the needs of the community members; 3) Since the earthly Church serves so that an individual may meet God, the pastoral authority is exclusively at the service of the meeting between the Church and the heavenly Jerusalem. Fatherhood is a ministry of meeting and helping in growing up to the meeting between man and God.